A Guide to Treatments That Work 2007
DOI: 10.1093/med:psych/9780195304145.003.0010
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Treatments for Major Depressive Disorder

Abstract: Behavior therapy (BT), cognitive-behavior therapy (CBT), and interpersonal psychotherapy (IPT) have each been shown by at least two Type 1 or Type 2 randomized controlled trials, as well as by four meta-analytic reports of the literature, to be effective psychosocial interventions for patients meeting criteria for major depressive disorder (MDD). All three psychosocial treatments have yielded substantial reductions in scores on the two major depression rating scales (the Beck Depression Inventory and the Hamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
68
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 0 publications
0
68
0
Order By: Relevance
“…Based on current guidelines for the primary care population, problem-solving therapy, interpersonal psychotherapy (IPT), and cognitive-behavioral therapy (CBT) have demonstrated efficacy in the treatment of depression, with CBT and IPT reducing symptoms as efficaciously as pharmacology [40,41]. Psychotherapy is also a valuable augmentation strategy for treatment-resistant or chronic MDD, with polytherapy often superior to medication alone [42,43].…”
Section: Psychotherapeutic Interventionsmentioning
confidence: 99%
“…Based on current guidelines for the primary care population, problem-solving therapy, interpersonal psychotherapy (IPT), and cognitive-behavioral therapy (CBT) have demonstrated efficacy in the treatment of depression, with CBT and IPT reducing symptoms as efficaciously as pharmacology [40,41]. Psychotherapy is also a valuable augmentation strategy for treatment-resistant or chronic MDD, with polytherapy often superior to medication alone [42,43].…”
Section: Psychotherapeutic Interventionsmentioning
confidence: 99%
“…A typical finding for depression (in double blind clinical trials) is that either drugs or weekly therapy will lift about half of the treated patients out of depression within four months. After successful treatment the risk of relapse is greater for those treated with drugs, unless they keep on taking them (figure) 13 14 15. Thus the cost effectiveness of the two approaches is similar, but many people refuse drugs because of side effects and because they want to feel more in control of their emotions.…”
Section: Cost Effective Treatmentsmentioning
confidence: 99%
“…There are a substantial number of studies examining treatments for depression or alcohol-related disorders separately. For example, interpersonal psychotherapy (IPT; Weissman and Markowitz, 2002) and cognitive and behavioral interventions (cognitive-behavioral therapy; CBT; Craighead et al, 1998) have demonstrated efficacy with depressive disorders; CBT, 12-step, and relapse prevention have been shown to be efficacious in the treatment of alcoholism (e.g., Finney et al, 1999;Irvin et al, 1999;Project Match Research Group, 1997, 1998. However, few studies have examined treatments for patients with depression and a comorbid alcohol-related disorder.…”
Section: Treatments For Substance-related Disorders and Comorbid Deprmentioning
confidence: 99%
“…Disease-specific treatments have been shown to be efficacious for individuals diagnosed with substance use or other psychiatric disorders alone (e.g., Craighead et al, 1998;Finney et al, 1999;Weissman and Markowitz, 2002). While a number of theoretical models have been developed to explain the onset and maintenance of comorbidity (see Mueser et al, 1998;Verheul and van den Brink, 2005), there are still little data supporting one model over another.…”
mentioning
confidence: 99%